1981
DOI: 10.1021/jm00135a011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of 2-alkyl-3-hydroxy-1,4-naphthoquinones against Theileria parva

Abstract: A variety of naphthoquinones have veen prepared and evaluated in vitro against the causative agent of the cattle disease East Coast Fever-Theileria parva infection. It is concluded from structure-activity studies that a 2-hydroxyl moiety es essential for high activity. The most active compounds tested were 2-hydroxy-3-alkyl-1,4-naphthoquinones in which the alkyl moiety was cyclohexyl, cyclohexylcyclohexyl, tridecyl, or tetradecyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…[292] Interestingly, activity against Theileria parva infections in cattle was observed which led to extensive structural variations, resulting in parvaquone (86), a highly efficient therapeutic of the Theileria parva infection. [293] Subsequently, the cyclohexyl residue of parvaquone was widely explored, leading to the compound BW58C80 (87), which has broad antiprotozoal activity. [294] In humans, the tert-butyl residue is rapidly hydroxylated to the 1000-fold less active metabolite.…”
Section: Development Of 2-hydroxynaphthoquinonesmentioning
confidence: 99%
“…[292] Interestingly, activity against Theileria parva infections in cattle was observed which led to extensive structural variations, resulting in parvaquone (86), a highly efficient therapeutic of the Theileria parva infection. [293] Subsequently, the cyclohexyl residue of parvaquone was widely explored, leading to the compound BW58C80 (87), which has broad antiprotozoal activity. [294] In humans, the tert-butyl residue is rapidly hydroxylated to the 1000-fold less active metabolite.…”
Section: Development Of 2-hydroxynaphthoquinonesmentioning
confidence: 99%
“…The most efficacious vaccine approach for East Coast fever was developed many years ago and includes infection of cattle with T. parva sporozoites and immediate treatment with a drug that impairs the establishment of infection, such as oxytetracycline (6) or, alternatively, buparvaquone (BPQ), which is currently the only effective compound for the treatment of bovine theileriosis (7)(8)(9). BPQ is a hydroxynaphtoquinone related to parvaquone (10,11). To be effective, the compound must be administered during the early stage of infection, and the drug is not always affordable or available to farmers (12).…”
mentioning
confidence: 99%
“…Atovaquone (2-[trans-4-(4Ј-chlorophenyl)cyclohexyl]-3-hydroxy-1,4-hydroxynaphthoquinone) (2, 3) is an anti-protozoal compound that has broad-spectrum activity against apicomplexan parasites including Plasmodium (4), Toxoplasma (5), Theileria (6), and Babesia (7) and the fungus Pneumocystis carinii (8). The effects of the drug on cell respiration and the structural similarities of atovaquone and ubiquinol suggested that the bc 1 complex was the target (4).…”
mentioning
confidence: 99%